Do Global Factors Drive Herd Behavior in Asymmetric: Evidence from Indonesia, Malaysia, and Thailand - Gusni, Gusni; Komariah, Siti; Riantani, Suskim (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The occurrence of several crises in recent decades has led to significant uncertainty in the capital market, potentially fostering tendencies for herd behavior. This conduct may manifest in situations of asymmetry when the market experiences varying conditions (market up and down). Herd behavior in asymmetric can be driven by a variety of global influences, such as the Federal Funds Rate and the world oil price. The aim of this research is to investigate whether herd behavior exists under asymmetric conditions, and to explore the influence of global factors on such behavior within the manufacturing sectors listed in the capital markets of Indonesia, Malaysia, and Thailand using daily closing stock price information from January 2015 to December 2022. This research utilizes a cross-sectional dispersion methodology and incorporates a dummy variable within the standard model to accomplish its research objective. The findings denote that asymmetric herding tendencies are evident solely among manufacturing firms listed on the Indonesian stock market during downturns, contrasting with the absence of such behavior in Malaysia and Thailand during market fluctuations. In Indonesia, global factors do not play a significant role in prompting asymmetric herding, whereas in Malaysia and Thailand, are more influenced by the Federal Funds Rate. Keywords: Asymmetric Herding; Market Up and Down; Federal Funds Rate; World Oil Price; Cross-Sectional Dispersion